Beneficial Effects of Melatonin for the Newborn - Reza Saeidi (Iranian Journal of Neonatology, 2024)
Melatonin (N-acetyl-5-methoxytryptamine) is secreted by the pineal gland, retina, gut, bone morrow, cerebellum, skin, placenta(1).It controls the circadian rhythm,inflammation, energy metabolism, reproductive physiology, and fetal development(2, 3).The production of melatonin is activated after birth, but it lacks the rhythmic secretion until 3–5 months after birth(4). Some evidence supports the idea that therapeutic use of melatonin during pregnancy and lactation period may reduce materno-fetal complications.Free radicals and Oxidative stress play well known role in some newborn diseases and Beneficial effects of melatonin have been reported in cardiovascular and CNS disease, sleep disorders, prevent or treatment of neonatal diseases like sepsis, bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), necrotizing enterocolitis (NEC).(5-7)some scientists have been used; melatonin as an adjuvant in the treatment of term and preterm newborns special when we know, preterm infants have melatonin deficiency.Although side effects of oral melatonin supplements at low doses in the short term are minimal, Some study report; Drowsiness (drow-siness), headache, diarrhea,irritability, restlessness, insomnia, anxiety, lethargy, psychomotor hyperactivity, High blood pressure, abdominal pain, itching, glycosuria, proteinuria, abnormal liver function tests, weight gain, fatigue(8).However, more studies are needed to confirm the beneficial effects of preventive and therapeutic strategies of melatonin.